Feral fascists and deep green guerrillas: infrastructural attack and accelerationist terror. Issue 1 (2nd January 2022) - Loadenthal, Michael
ABSTRACT: The modern accelerationist far-right has a notable focus on attacking and disrupting sites of infrastructure – energy delivery, mass transportation, mass communication, etc. – as part of its wider strategy to provoke socio-political systemic breakdown, in the hopes of accelerating social change. While traditionally fascist and adjacent elements of the far-right focused on intimidating racial, ethnic, and religious minorities, some elements of this movement have shifted focus towards ecological issues, and in doing so, begun to focus their strikes on these accessible, physical embodiments of "the system." Although diverging wildly in their revolutionary and prefigurative focus, some leftist movements share this counter-infrastructural focus, although pursue their targets with the utmost protection of human and animal life. For the ecofascist far-right, the networks' porous malleability in modernity permits crosspollination with the left, as well as more fringe communities such as those based in Satanism, and the so-called "eco-extremist tendency." This analysis focuses on the discourses formed by content made by accelerationist-ecofascists and leftist eco-saboteurs, using the Telegram messaging platform. Through a visual and text-based discursive analysis supported by corpus linguistics, these themes are laid bare and adopted as a basis for discussing a revolutionary response to counter-systemic violence situated in conflict transformation and ecological justice.